A Rapid Growth of Verrucous Carcinoma After Biopsy: Treatment and Reconstruction - Budhipramono, Angelica Gracia; Pribadi, Sweety (Lingkar Studi Bedah Plastik Foundation, 2021)
Summary: An increasing amount of evidence from clinical and experimental studies suggests that biopsies, thought to assist with definitive diagnoses, may aggravate tumor progression. We present a case of fast-growing giant verrucous squamous cell carcinoma, observed two weeks following biopsy. A 38-year-old man presented with a nose tumor that recurred two weeks after a biopsy and debridement to remove a lesion that was thought to be an abscess. Wide excision was performed on the tumor, frozen sectioned; the defect was reconstructed with a two-step forehead flap. The rapid tumor growth observed in this case raises the question of whether biopsies or other interventions may accelerate the growth of malignant tumors. Verrucous squamous cell carcinoma is slow-growing with a predilection for oral and nasal mucosa and rarely metastasizes. The patient presented here is an unusual case, with a tumor rapidly growing within fifteen days. A two-staged paramedian forehead flap is the workhorse of nasal reconstruction. Even though the benefit of doing biopsies overall outweighs the potential side effects, further research is required to determine whether biopsies affect the progression of the tumor. Early differential diagnosis is also crucial, as it may affect the patient's plan of treatment and prognosis. Giant tumors on the facial area may cause a functional and cosmetic disturbance. A two-step forehead flap produces a satisfactory cosmetic appearance for the patient one-year post-procedure.